Illustration of Typical Scenarios of Fire and Explosion Accidents Caused by Runaway Reactions to Support the Implementation of Risk Assessment in Small and Medium Enterprises - Yoshihiko Sato; Yukiyasu Shimada; Haruhiko Itagaki (Chemical Engineering Transactions)
Unintended chemical reactions involving handled substances are often less understood compared to those involving flammable substances. As a result, risk assessment and corresponding risk reduction measures (hereafter referred to as “RA”) may be insufficient in addressing the hazards associated with fire and explosion accidents caused by unintended reactions. Furthermore, conducting effective RA requires extensive knowledge and experience specific to the target process. However, small and medium-sized enterprises (SMEs) often face challenges in identifying and implementing appropriate risk reduction measures due to limited expertise and experience. One practical approach to assisting SMEs is to provide typical scenarios of critical events, such as runaway reactions, along with corresponding risk reduction measures. Additionally, identifying and prioritizing the most probable scenarios from among the typical cases can help SMEs focus on the most relevant risk reduction measures. To facilitate RA implementation in SMEs, this study developed and consolidated typical fire and explosion accident scenarios caused by runaway reactions into a single scenario diagram. Moreover, past incidents of fires and explosions triggered by runaway reactions were analyzed and mapped to these typical scenarios, allowing the identification of frequently occurring patterns. Risk reduction measures are also provided for the most recurrent scenarios to support effective risk reduction efforts.